Stress Testing of Financial Systems : An Overview of Issues, Methodologies, and FSAP Experiences - Martinez Peria, Maria; Blaschke, Winfrid; Jones, Matthew; Majnoni, Giovanni (Washington, D.C. : International Monetary Fund, 2001)
The paper has three objectives. After a general introduction to some of the concepts and basic techniques of stress testing, the paper gives an overview of some of the conceptual issues involved in evaluating risks at the aggregated level of financial systems. Second, this study provides a basic framework and toolkit for conducting stress tests. Finally, the paper reviews some of the stress-testing analyses conducted in the context of the Financial Sector Assessment Program (FSAP) and suggests simplified approaches to deal with situations where the quantity and quality of the data is less than ideal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet